Kajian Dieng Culture Festival sebagai Implementasi Etnopedagogi Materi Biologi pada Kurikulum Merdeka: (Study of the Dieng Culture Festival as an Ethnopedagogy Implementation of Biology Material in the Independent Curriculum) - Fadilah, Solikhah Isti; Sriyati, Siti; Irawan, Tb Moh Irma Ari (BIODIK, 2023)
The independent curriculum is a curriculum concept designed to provide more leeway, flexibility, and autonomy to schools in Indonesia. This concept aims to increase the relevance of education by accommodating the unique developmental needs of each student. The independent curriculum understands that each school and student have different needs and potential. The potential for diversity and different customs in each region of Indonesia provides great opportunities for developing educational materials using local wisdom. It turns out that Indonesia's local wisdom has not been studied much, so it requires scientific study so that it can be used in learning activities. One of the local wisdoms that researchers want to study is the Dieng Culture Festival. This study was carried out using the literature review method. The search results found around 337 articles, which were then selected according to relevant topics. Next, the researcher compiled the literature findings. The results found regarding the Dieng Culture Festival were the study of the phenomenon of dreadlocks and the purwoceng plant as the most prominent local wisdom in the festival. The results of studies related to the phenomenon of dreadlocks and purwoceng plants can scientifically add to the ethnopedagogical studies used by teachers in conducting learning according to the independent curriculum. The results of an ethnoscientific study of the dreadlocks phenomenon can support learning activities in high school phase F material on the concept of inheritance. Studies related to the endemic plant Pimpinella prutjan molk can be used as supporting material for the diversity of living creatures and their roles, as well as phase E biological technology innovations. Key words: Local wisdom, ethnosaince, ethnopedagogy, Dieng dreadlocks, Pimpinella prutjan, Molk. Abstrak. Kurikulum merdeka merupakan konsep kurikulum yang dirancang untuk memberikan lebih banyak kelonggaran, fleksibilitas, dan otonomi kepada sekolah-sekolah di Indonesia. Konsep ini bertujuan untuk meningkatkan relevansi pendidikan dengan mengakomodasi kebutuhan yang unik pada perkembangan setiap siswa. Kurikulum merdeka memahami bahwa setiap sekolah dan siswa memiliki kebutuhan dan potensi yang berbeda. Potensi keanekaragaman dan adat istiadat yang berbeda pada setiap daerah Indonesia memberikan peluang yang besar dalam pengembangan materi pada pendidikan menggunakan kearifan lokal (local wisdom). Local wisdom yang dimiliki Indonesia ternyata belum banyak dikaji sehingga memerlukan kajian secara sains agar dapat digunakan dalam kegiatan pembelajaran. Salah satu kearifan lokal  yang ingin dikaji peneliti adalah Dieng Culture Festival. Kajian ini dilakukan dengan metode literature review. Hasil pencarian ditemukan sekitar 337 artikel, kemudian diseleksi sesuai dengan topik yang relevan. Selanjutnya peneliti melakukan kompilasi dari  temuan  literatur.  Hasil yang ditemukan terkait Dieng Culture Festival yaitu ditemukannya kajian fenomena rambut gimbal dan tanaman purwoceng sebagai local wisdom yang paling menonjol dalam festival tersebut. Hasil kajian terkait fenomena rambut gimbal dan tanaman purwoceng  secara sains dapat menambah kajian ethnopedgogi yang digunakan guru dalam melakukan pembelajaran sesuai kurikulum merdeka. Hasil kajian etnosains fenomena rambut gimbal dapat mendukung kegiatan pembelajaran pada materi SMA fase F materi konsep pewarisan sifat. Kajian terkait tanaman endemik Pimpinella prutjan molk dapat digunakan sebagai pendukung materi keanekaragaman makhluk hidup dan peranannya serta inovasi teknologi biologi fase E. Kata kunci: Kearifan lokal, etnosains, etnopedagogi, rambut gimbal Dieng, Pimpinella prutjan, Molk